THE ROLE OF INTERACTIVE TECHNOLOGIES IN DEVELOPING COMPOSITIONAL THINKING IN PAINTING CLASSES (Multidisciplinary Journal of Science and Technology, 2026)
This article substantiates, from a scientific and pedagogical perspective, the role of interactive technologies in developing compositional thinking in painting classes. The essence and content of compositional thinking, its structural components, and its significance in painting education are analyzed. Furthermore, the didactic potential of interactive technologies—such as brainstorming, small group work, problem-based learning, reflection, and project-based instruction—in fostering compositional thinking is highlighted. The research findings demonstrate that an interactive approach contributes to the development of students’ independent thinking, creative decision-making, aesthetic taste, and analytical skills. The article also outlines the pedagogical conditions and methodological recommendations for organizing painting lessons on an interactive basis.